2015 IEEE Conference on Computer Vision and Pattern Recognition (CVPR) 2015
DOI: 10.1109/cvpr.2015.7298623
|View full text |Cite
|
Sign up to set email alerts
|

An efficient volumetric framework for shape tracking

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…A comparison of the result with those of three state-of-the-art methods (Liu et al, 2010;Bilir and Yemez, 2012;Allain et al, 2015) is listed in Table 3. The results support the intuitiveness of our method efficiency between neighboring frames.…”
Section: Model-level Interpolationmentioning
confidence: 99%
See 4 more Smart Citations
“…A comparison of the result with those of three state-of-the-art methods (Liu et al, 2010;Bilir and Yemez, 2012;Allain et al, 2015) is listed in Table 3. The results support the intuitiveness of our method efficiency between neighboring frames.…”
Section: Model-level Interpolationmentioning
confidence: 99%
“…A comparison with state-of-the-art methods (Liu et al, 2010;Bilir and Yemez, 2012;Allain et al, 2015) is shown in Table 4, which shows quantitative evaluation of the average reconstruction time per frame. Although the method of Bilir and Yemez (2012) showed a good result, our method still sped up the reconstruction.…”
Section: Model-level Interpolationmentioning
confidence: 99%
See 3 more Smart Citations